Cash Waqf Optimalization of Baitul Maal wat Tamwil in Indonesia: A Business Model Canvas Strategy - Umam, Khoirul; Aruni Mafaza, Syofi; Afifah Ahmad, Rusyda; Arif, Suyoto (Faculty of Sharia and Law, UIN Syarif Hidayatullah Jakarta, 2024)
This research aims to create a Cash Waqf model using a canvas model approach that can be applied to Islamic microfinance institutions (BMT), taking into account opportunities and challenges. The Analytic Network Process (ANP) method was employed in this research through interviews, Focus Group Discussions (FGD), and questionnaires processed with SuperDecision software. The research results indicate that, first, the researcher proposes a Cash Waqf microfinance fund model for BMT. Second, respondents showed a high level of agreement in selecting the criteria for the Cash Waqf model. Third, in its implementation, BMT will face opportunities such as the use of IT in management systems, the ability to reach out to the poor, special financing schemes, emotional closeness to customers, ease of customer access to offices, and MSME interest in this Cash Waqf micro fund model. The challenges faced include low public trust, lack of management certification, limited customer identification, competition with moneylenders, limited financing amounts, and suboptimal customer identification.Abstrak:Penelitian ini bertujuan untuk membuat model wakaf tunai menggunakan pendekatan model kanvas yang dapat diterapkan pada Lembaga Keuangan Mikro Syariah (BMT), dengan mempertimbangkan peluang dan tantangan. Metode Analytic Network Process (ANP) digunakan dalam penelitian ini melalui wawancara, FGD, dan kuesioner yang diolah dengan software SuperDecision. Hasil penelitian menunjukkan bahwa, pertama, peneliti mengusulkan model dana keuangan mikro wakaf tunai untuk BMT. Kedua, responden menunjukkan kesepakatan yang tinggi dalam memilih kriteria model wakaf tunai. Ketiga, dalam penerapannya, BMT akan menghadapi peluang seperti: penggunaan IT dalam sistem pengelolaan, kemampuan merangkul masyarakat miskin, skema pembiayaan khusus, kedekatan emosional dengan nasabah, kemudahan akses nasabah ke kantor, dan minat UMKM terhadap model dana mikro wakaf tunai ini. Tantangan yang dihadapi meliputi: rendahnya kepercayaan masyarakat, kurangnya sertifikasi pengelola, identifikasi nasabah, persaingan dengan rentenir, keterbatasan jumlah pembiayaan, dan identifikasi nasabah yang belum optimal.